Variation of antibiotic consumption and its correlated factors in Turkey - AKICI, AHMET (SPRINGER HEIDELBERG, 2017)
Background Presentation of antibiotic utilization data by reliable and comparable analyses constitutes an important way of ensuring rational use of antibiotics. This study aimed to evaluate antibiotic consumption (AC) of Turkey by each city/region and to investigate any association of such consumption with socio-economic factors. Method For 81 provinces and 12 regions in Turkey, AC data from IMS (Intercontinental Medical Statistics) in 2011 was analyzed in accordance with ATC/DDD, DID (Anatomical Therapeutic Chemical/Defined Daily Doses, DID = DDD/1000 inhabitants/day) methodology supported by World Health Organization. Association between provincial AC rates and socio-economic development index (SEDI)-2011 and between regional AC rates and some health indicators were analyzed. Results While provincial AC data of Turkey was detected to vary between 17.2 and 55.2 DID (Hakkari and Usak, respectively), regional AC ranged from 28.4 to 48.9 DID (Middle Eastern Anatolia and Western Anatolia, respectively). Mostly consumed antibiotic group among all regions were beta-lactamase inhibitor/penicillin combinations (range: 9.9-17.6 DID). SEDI and AC of each city showed positive correlation (rho = 0.683, p < 0.001). While regional AC was positively associated with percentage of 14-year-old population (p = 0.002) and pharmacist density (p < 0.001), it was negatively associated with physician density (p = 0.038). Conclusion It is remarkable that Turkey, at both provincial and regional levels, exhibits important variations in AC, which is proportional to socio-economic status. Besides, the consumption is found to be closely associated with recognized critical factors of access to healthcare. These findings are expected to provide important insights to the activities promoting rational use of antibiotics.
Keywords: Defined daily dose; Inhabitants; Antibiotic utilization; Rational antibiotic use; Socio-economic factors; CROSS-NATIONAL DATABASE; EUROPE; RESISTANCE; GERMANY; TRENDS; CARE